Evaluating the Effectiveness of Disaster Management Service Policy: Evidence from West Sumatra, Indonesia - Mulia, Rizki Afri; Hendrik, Doni (LPPM Universitas Ekasakti, 2025)
Disaster management policy is increasingly expected to function as a reliable public service system across preparedness, response, and recovery. However, effectiveness is often inferred from completion-oriented indicators that may not capture service quality, coordination experience, or adaptive capacity. This study evaluates the effectiveness of disaster management service policy in West Sumatra, Indonesia, through qualitative document analysis of official provincial and national documents (2020–2025), focusing on the 2022–2024 planning and performance cycle. The corpus includes provincial regulation, strategic and annual plans, operational and coordination instruments, and performance accountability reports. Analysis followed a structured document-analysis workflow and reflexive thematic analysis to trace policy intent, implementation instruments, resourcing signals, performance indicators, and learning. Results show consistently high reported achievement on coverage/completion indicators in 2022–2023, alongside a notable decline in stakeholder satisfaction in 2023, indicating a gap between administrative attainment and experienced service quality. Documents also identify persistent constraints in operational facilities and support systems. The 2024 work plan signals adaptive intent by strengthening preparedness and risk-information services and specifying capacity-building outputs. Overall, West Sumatra’s disaster management service policy appears administratively strong but quality-vulnerable, underscoring the need for quality-sensitive performance indicators, strengthened enabling capacity, and institutionalized coordination and learning loops.